Quantification of specific T and B cells immunological markers in children with chronic and transient ITP. Issue 12 (22nd May 2017) - Levy‐Mendelovich, Sarina; Lev, Atar; Aviner, Shraga; Rosenberg, Nurit; Kaplinsky, Caim; Sharon, Nechama; Miskin, Hagit; Dvir, Aviya; Kenet, Gili; Schushan, Irit Eisen; Somech, Raz
Abstract: Background: Immune thrombocytopenic purpura (ITP) is characterized by a transient (nonchronic) or permanent (chronic) decline in the number of platelets. Predicting the course of ITP, at the time of diagnosis, is of importance. Here we studied at diagnosis, clinical and immunological parameters in order to distinguish between different courses. The latter included the measure of new B and T cells using quantification of kappa‐deleting recombination excision circles (KRECs) and T‐cell receptor excision circles (TRECs), respectively. Methods: Blood samples were collected from 44 children with a clinical diagnosis of ITP. Real‐time PCR was performed in order to quantify the number of copies of TREC and KREC followed by collection of clinical data from medical files. The children were retrospectively divided into two groups: chronic and nonchronic. Results: Twenty‐four patients (54%) were classified as nonchronic ITP and 20 patients (46%) were classified as chronic ITP. We confirmed some clinical parameters (e.g., gender, age) but not others (e.g., preceding infection, level of thrombocytopenia) that distinguish patients with chronic and nonchronic course. While KREC quantification was similar in patients regardless the outcome of their disease, it was significantly higher than the level of controls ( P < 0.05). TREC quantification was not different between patients and controls. Conclusions: KREC but not TREC levels are different in patients comparing to controls, pointing to an overreaction of B‐cell development as a role in the pathogenesis of ITP. These results may shed more lights on the immune mechanism of ITP.